PENGARUH KOMPOSISI PEREKAT TERHADAP EMISI FORMALDEHIDA DAN SIFAT FISIS-MEKANIS PAPAN PARTIKEL - Paribotro Sutigno; Suwardi Sumadiwangsa (Jurnal Penelitian Hasil Hutan, 1986)
One  of  the  drawbacks   of  using particleboard   bonded  with  urea formaldehyde  (UF)  is the  formaldehyde  emission, especially  in a room  with  limited  ventilation.  Some  countries  have imposed  restriction  of allowable  emission  for certain  uses.This  work  deals  with  the  study   on  the  effect   of  the  use of  variety  of  hardeners  types  and percentages   of  melamin formaldehyde (MF) as fortifier   on formaldehyde    emission.   The experiment   reveals that  the effect  of hardener  mixed  with catching  agent  and the effect  of fortifier on formaldehyde   emission  was effective   to curb  down  the formaldehyde   emission.The effect  of fortifier   on some physical  and mechanical properties   was observed.  It decreases water absorption  and thickness swelling,  increases shear strength;  internal  bond  strength,   and  the  modulus  of rupture,   but  did  not  affect  the modulus  of elasticity.The effect  of hardener  mixed  with  catching  agent on modulus  of  elasticity  was not significant,  while on other  particle- board properties   the  effect   was not  consistent.